Kaumātua needs and perspectives regarding urban papakāinga: a mixed methods observational study - Danielle Lee Smith; John G. Oetzel; Mary L. Simpson; Yvonne Wilson; Sophie Nock; Rangimahora Reddy (Kōtuitui)
Safe, secure, suitable housing is often an unattainable reality for kaumātua (older Māori aged 55 years and over in this study) in Aotearoa New Zealand. Kaumātua, unfortunately, are at the forefront of the housing crisis, and struggle to find housing which meets their most basic needs. Therefore, many organisations are considering the development of urban papakāinga to meet their needs. The purpose of this study is to assess the needs of kaumātua currently in temporary, emergency or state housing situations to understand their perspectives about what factors enable successful urban papakāinga. The research design and methodology in this article apply a multi-method observational approach, guided by the He Pikinga Waiora (HPW) Implementation Framework. The main findings in this study include five cultural characteristics necessary within urban papakāinga developments; whanaungatanga (connections); kaitiakitanga (environmental care/ guardianship); manaakitanga (care for others); rangatiratanga (leadership, autonomy, or control); and haumarutanga (safety/security). In addition, key correlates of wellbeing indicators included housing suitability, community connection and a safe neighbourhood. These key needs and perspectives have important theoretical and practical implications for kaumātua wellbeing, and successful housing developments for Māori.Glossary of Kupu Māori words: Aotearoa: Māori name of New Zealand; haumarutanga: security, safety, or peace of mind; kaitiakitanga: environmental care, guardianship, or stewardship; kaumātua: older Māori aged 55 years and over; kaupapa Māori: Māori approach; koroua: older male; kuia: older female; manaakitanga: generosity, cherish, respect, care and hospitality; Māori: Indigenous people of Aotearoa-NZ; papakāinga: traditional Māori housing/community complex; Papatūānuku: Earth Mother; rangatiratanga: leadership, self-determination, autonomy, or control; Te Puāwaitanga o Ngā Waka: The Blossoming of Aspirations for All; tikanga: correct custom, procedure, or protocol; tūrangawaewae: a place of strength, belonging, connection, a place to stand; urban papakāinga: modern Māori housing/urban intergenerational village; wairuatanga: spirituality; whakapapa: decent, lineage, ancestor, or genealogy; whānau: family or closely connected kin group; whanaungatanga: connectedness, kinship, or relationships